Some Choreographic Notes on the Dance of Theory with Data - Chaney, Marvin L. ca. 20./21. Jahrhundert (2016)
This volume is a tour de force that exceeds any predecessor in its theoretical scope. Even more important than its intriguing syntheses are its probing questions, its analytical categories and tools, and its challenges to easy assumptions. Boer’s pursuit of theoretical integration, however, sometimes leads him to overgeneralize. He staunchly maintains, for example, that arable land was plentiful in all times and places in ancient Southwest Asia. Comprehensive archaeological surveys of the southern Levant tell a different story. The Iron ii population was more than double that of the Bronze Age or of Iron i. The highlands particularly witnessed the occupation of marginal niches. Population pressure on arable land was a reality in Iron ii Palestine. Similarly, the many standardized wine amphorae recovered from two eighth-century bce. Phoenician ships sunk off the Philistine coast contradict Boer’s repeated insistence that there is no evidence for long-distance trade in bulk goods.
Keywords: Régulation theory -- extractive economics (in Ancient Southwest Asia) -- population pressure (in Ancient Southwest Asia) -- scarcity of arable land (in Ancient Southwest Asia) -- trade in bulk goods (in Ancient Southwest Asia) -- maritime societies